Taxonomy, systematics and biology of the Australian halotolerant wolf spider genus Tetralycosa (Araneae: Lycosidae: Artoriinae) - Framenau, Volker W.; Hudson, Peter (European Journal of Taxonomy, 2017)
The Australian wolf spider genus Tftralycosa Roewer, 1960, with Lycosa meracula Simon, 1909 (junior synonym of Lycosa oraria L. Koch, 1877) as type species, is revised to include 13 species, eight of which are described as new here: Tetralycosa adarca sp. nov., T. alteripa (McKay, 1976), T. arabanae Framenau, Gotch & Austin, 2006, T. baudinettei sp. nov., T. caudex sp. nov., T. eyrei (Hickman, 1944), T. floundersi sp. nov., T. halophila sp. nov., T. oraria (L. Koch, 1876), T. orariola sp. nov., T. williamsi sp. nov., T. wundurra (McKay, 1979) comb. nov. and T. rebecca sp. nov. Members of Tetralycosa are halotolerant, exclusively inhabiting saline environments such as coastal beaches, and mound springs, clay pans and salt lakes in the Australian interior. A phylogenetic analysis of the genus identified a monophyletic clade of eight species that live permanently on the barren surface of salt lakes suggesting a single radiation into this extremely inhospitable habitat. Some of these Tetralycosa species are currently known from single salt lakes only and with increasing disturbances of these systems by mining, agriculture and recreational use, research effort should be increased to study their ecology and conservation status.